Konvergensi antara Liberalisme dan Kolektivisme sebagai Dasar Etika Politik di Indonesia - Siswanto, Dwi (Jurnal Filsafat "WISDOM", 2004)
The polical ethics in matters peratining to the state possess a strategic menaning as a reference understanding of the development of human nature. Beside that, the political ethics has a function as a tool of analysis for question and clarification toward a political legitimate which responbility, rationality, objectivity, and argumentatively; not depend on emotion and apriori.Indonesia's political ethics based on Pancasila seem a convergence between liberalism and collectivism, although The Pancasila values rooted in Indonesian real life. Anthropological of The Indonesia's political ethics based on the human nature are "monopluralis" and bipolar structure. According to Pancasila doctrine, man has special characteristic as individual and social creature. In that characteristic is form of convergence liberalism and collectivism. That implication not every person but also goverments in all their activities must to directive the princple of the Pancasila's political ethics, namely respect for equality, liberty, solidarity, and subsidiarity.